Teachers’ Pedagogical Efforts in Strengthening Students’ Qur’anic Literacy in Pesantren-Based Schools - M. Fany Fahrulsyah; Rofi'ah, Siti (Journal Of Islamic Education And Pesantren, 2024)
Qur’anic literacy encompasses the ability to read, write, understand, and translate the Qur’an as an integral dimension of religious literacy in Islamic education. Strengthening Qur’anic literacy cannot be separated from teachers’ pedagogical roles, particularly in pesantren-based schools where the Qur’an is culturally positioned at the center of learning. However, in practice, students continue to face various difficulties in reading and understanding the Qur’an, which necessitates systematic and sustained pedagogical interventions by teachers. This study aims to analyze teachers’ efforts in strengthening students’ Qur’anic literacy at SMP Al-Furqan Madrasatul Qur’an Tebuireng Jombang. Employing a qualitative approach with a case study design, data were collected through observations, in-depth interviews, and documentation involving the principal, the vice principal for curriculum affairs, Qur’an teachers, and students. The findings reveal that Qur’anic literacy is strengthened through structured learning practices, including daily habituation of Qur’anic reading using the talaqqi method, recitation assessment (setoran), individualized mentoring based on students’ abilities, teachers’ role modeling in religious practices, and continuous recitation evaluation. These findings underscore that Qur’anic literacy is not merely the outcome of religious routines, but is shaped by teachers’ systematic and adaptive pedagogical interventions within the framework of pesantren-based Islamic education.